REAL-TIME MACHINE LEARNING MODEL MONITORING: A FRAMEWORK FOR DRIFT DETECTION AND PERFORMANCE MANAGEMENT - Apurva Reddy Kistampally (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article explores the transformative impact of Artificial Intelligence (AI) and Machine Learning (ML) in monitoring production models, presenting a comprehensive framework for real-time drift detection and performance management. The article examines advanced monitoring architectures integrating continuous data analysis, automated alert systems, and sophisticated visualization tools to maintain model reliability and performance. Through article analysis of distributed computing implementations and dashboard design considerations, the article demonstrates how organizations can effectively detect and respond to model degradation, data drift, and performance issues. The framework encompasses multiple layers of monitoring, from system-level metrics to user experience optimization, while incorporating emerging technologies such as IoT and edge computing. The article investigates implementation strategies across various industries, presenting case studies validating comprehensive monitoring solutions' effectiveness. By addressing challenges in model maintenance, data drift detection, and performance optimization, this article provides a structured approach to building resilient ML monitoring systems that ensure sustained model performance and reliability in production environments.